Gas Phase Protonation of Enamines - Raymond Houriet; Jürgen Vogt; Edwin Haselbach (CHIMIA)
The proton affinities and ionization energies of several enamines and of the corresponding saturated amines have been determined. From these data the hydrogen affinities of the molecular cations were calculated. The results yield energetic and structural insight into the protonation reaction of enamines in the gas phase.